2019
DOI: 10.7554/elife.43281
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sounds and actions in early auditory cortex of nonhuman primates

Abstract: An individual may need to take different actions to the same stimulus in different situations to achieve a given goal. The selection of the appropriate action hinges on the previously learned associations between stimuli, actions, and outcomes in the situations. Here, using a go/no-go paradigm and a symmetrical reward, we show that early auditory cortex of nonhuman primates represents such associations, in both the spiking activity and the local field potentials. Sound-evoked neuronal responses changed with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…This is in accordance with the findings that neurons in these layers convey information to downstream motor centers, as the basal ganglia or the striatum, which play an important role for the control of motor decisions by the sensory cortex (Xiong et al, 2015;Znamenskiy and Zador, 2013). Further, the selection of an appropriate action might also be conveyed directly to motor cortex via direct anatomical projections (Matyas et al, 2010;Huang et al, 2019). Ample evidence argues that our findings reflect a motor-related modulation of the cortical physiology, rather than a movement artifact.…”
Section: Correlates Of Motor Initiation Dominate A1 Population Activisupporting
confidence: 92%
See 3 more Smart Citations
“…This is in accordance with the findings that neurons in these layers convey information to downstream motor centers, as the basal ganglia or the striatum, which play an important role for the control of motor decisions by the sensory cortex (Xiong et al, 2015;Znamenskiy and Zador, 2013). Further, the selection of an appropriate action might also be conveyed directly to motor cortex via direct anatomical projections (Matyas et al, 2010;Huang et al, 2019). Ample evidence argues that our findings reflect a motor-related modulation of the cortical physiology, rather than a movement artifact.…”
Section: Correlates Of Motor Initiation Dominate A1 Population Activisupporting
confidence: 92%
“…Motor initiation has been reported before to enhance or suppress sensory-driven activity in other (primary) sensory cortices depending on region, system and taskengagement (Busse et al, 2017;Steinmetz et al, 2019). From our data we hypothesize, that, during the detection, the tone-evoked activity in the primary auditory cortex may be modulated by auditory-guided motor initiation (Brosch et al, 2015;Huang et al, 2019;Niwa et al, 2012a). The distinct sound frequency of a pure tone seems less determining on the activity strength.…”
Section: Correlates Of Motor Initiation Dominate A1 Population Activimentioning
confidence: 72%
See 2 more Smart Citations
“…Previous work has shown that AC neurons can encode non-sensory, choice-related activity (Huang, Heil et al 2019). The Huang et al study found that whether a response was predictable following a cue tone, based on the task condition, affected neural responses in AC to the tone.…”
Section: Discussionmentioning
confidence: 98%